2006
DOI: 10.1007/s00221-006-0473-z
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamic properties of hyperpolarization-activated current (Ih) in a subgroup of primary sensory neurons

Abstract: Ih is a poorly selective cation current that activates upon hyperpolarization, present in various types of neurons. Our aim was to perform a detailed thermodynamic analysis of Ih gating kinetics, in order to assess putative structural changes associated with its activation and deactivation. To select dorsal root ganglia neurons that exhibit large Ih, we applied a current signature method by Petruska et al. (J Neurophysiol 84:2365-2379, 2000) and found appropriate neurons in cluster 4. Currents elicited by 3,00… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
12
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 56 publications
2
12
0
Order By: Relevance
“…I h is an inward (depolarizing) Na ϩ /K ϩ current carried by hyperpolarization-activated cyclic nucleotide gated (HCN) channels. Consistent with evidence that cooling inhibits I h (11,37,40), we found cooling eliminated the depolarizing voltage "sag" caused by activation of I h during negative current injection (47). Inhibition of an excitatory membrane current associated with pacemaking is seemingly at odds with our findings that LC neurons intrinsically increase spontaneous discharge at cold temperatures.…”
supporting
confidence: 87%
“…I h is an inward (depolarizing) Na ϩ /K ϩ current carried by hyperpolarization-activated cyclic nucleotide gated (HCN) channels. Consistent with evidence that cooling inhibits I h (11,37,40), we found cooling eliminated the depolarizing voltage "sag" caused by activation of I h during negative current injection (47). Inhibition of an excitatory membrane current associated with pacemaking is seemingly at odds with our findings that LC neurons intrinsically increase spontaneous discharge at cold temperatures.…”
supporting
confidence: 87%
“…It has been shown in various types of preparation that the kinetics of I h is particularly sensitive to thermic conditions [20], [30], [31]. The temperature at which electrophysiological recordings are made, affecting both the amplitude and the kinetics of I h (Figure 4A), is one of the limiting factors in comparing the results; therefore, in this study most of the reported recordings were realized in precisely controlled temperature conditions.…”
Section: Resultsmentioning
confidence: 93%
“…These measurement errors are more pronounced for slow HCN channels than for the fast ones, and are highly dependent on temperature [19], [20]. Therefore, we have analyzed the dependence of the midpoint from the duration of the conditioning command.…”
Section: Resultsmentioning
confidence: 99%
“…For I h basal parameters were set as follows: ghbar_iar = 1e-5 S/cm 2 ; V h = −74.7 mV; maximum τ m value at −80 mV = 1010 ms. The Q 10 value of I h was set to 3 (Pena et al, 2006). The accuracy of the mathematical description of I h with respect to currents recorded at physiological temperature has been demonstrated before (Huguenard and McCormick, 1992).…”
Section: Methodsmentioning
confidence: 99%